ANALISIS KEPERCAYAAN DIRI SISWA KELAS 3 TERHADAP KEMAMPUAN MENULIS DI SDN 1 PANCASURA - Dita Sopyana; Resta Alinniah; Dea Asri Pujiasti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between self-confidence and learning enthusiasm of elementary school students through a mixed-methods approach. The primary issue addressed is the low student engagement in writing activities, triggered by a lack of self-confidence, with initial data indicating that 58.97% of students lack interest in conventional learning. The research employed an explanatory sequential design. Quantitative data were obtained through questionnaires administered to 39 third-grade students at SDN 1 Pancasura to measure self-confidence levels, while qualitative data were collected through observations and interviews with fourth-grade students to dissect the dynamics of learning enthusiasm. Quantitative results show that the majority of students fall into the "moderate" self-confidence category (41%), which significantly correlates with learning independence. Qualitative findings reveal that low learning enthusiasm is not caused by cognitive limitations but rather by psychological anxiety and high dependency on teacher instructions (62.30%). Data integration concludes that self-confidence acts as a primary mediator for students' intrinsic motivation. This study recommends strengthening affective aspects through positive reinforcement to break the cycle of motivational stagnation. The combination of both methods provides a comprehensive overview that improving literacy in elementary schools must begin with building a positive self-concept in students.